Differential immunomodulatory properties of Bifidobacterium logum strains: Relevance to probiotic selection and clinical applications - Medina, Marcela Susana (2007)
Modulation of host immunity is one of the proposed benefits of the consumption of probiotics. Nonetheless, comparative studies on the immunological properties that support the selection of strains of the same species for specific health benefits are limited. In this study, the ability of different strains of Bifidobacterium longum to induce cytokine production by peripheral blood mononuclear cells (PBMCs) has been evaluated. Live cells of all B. longum strains greatly stimulated regulatory cytokine interleukin (IL)-10 and proinflammatory cytokine tumour necrosis factor (TNF)-α production. Strains of the same species also induced specific cytokine patterns, suggesting that they could drive immune responses in different directions. The probiotic strain B. longum W11 stimulated strongly the production of T helper 1 (Th1) cytokines while B. longum NCIMB 8809 and BIF53 induced low levels of Th1 cytokines and high levels of IL-10. The effects of cell-surface components obtained by sonication of B. longum strains overall confirm the effects detected by stimulation of PBMCs with live cells, indicating that these components are important determinants of the immunomodulatory activity of B. longum. Genomic DNA of some strains stimulated the production of the Th1 and pro-inflammatory cytokines, interferon (IFN)-γ and TNF-α, but not that of IL-10. None of the cell-free culture supernatants of the studied strains was able to induce TNF-α production, suggesting that the proinflammatory component of these strains is associated mainly with structural cell molecules. The results suggest that despite sharing certain features, some strains can perform a better functional role than others and their careful selection for therapeutic use is desirable.